Revitalization the Function of Traditional Nagari Density in Handling Criminal Cases Based on Restorative Justice - Roni Efendi; Saadatul Maghfira; Hebby Rahmatul Utamy; Erwin Radon Ardiyanto (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The criminal justice system, which was previously focused on the criminal aspect or retributive perspective, is now confronted with the reality that there are only a few legal structures, ranging from judges, prosecutors, and police to a small number of prison institutions that serve as execution venues. The author is concerned with this legal fact, so he uses primary data sources and sociological juridical studies to try and find a remedy. According to the author's findings, to prevent the issues mentioned above, criminal cases in Minangkabau can be resolved through the Nagari Traditional Meeting Institution using the restorative justice idea, which aims to repair the social discord caused by criminal acts. When applying restorative justice, the Nagari Customary Association makes use of the relevant legal source of the Nan Salapan Law, while the formal legal procedures can use the Nan Duo Puluah Law.